2010
DOI: 10.1051/0004-6361/200912681
|View full text |Cite
|
Sign up to set email alerts
|

Radial velocities with CRIRES

Abstract: With the advent of high-resolution infrared spectrographs, radial relocity (RV) searches enter into a new domain. As of today, the most important technical question to address is which wavelength reference is the most suitable for high-precision RV measurements. In this work we use atmospheric absorption features as wavelength reference on CRIRES data obtained on two programs and three different targets. We analyzed the data from the TW Hya campaign again, reaching a dispersion of about 6 m/s on the RV standar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 36 publications
1
88
1
Order By: Relevance
“…Spectra were collected using the 4096 × 512 pixel Aladdin III detectors and a 0.2" slit which delivered a R∼100000 around 1598.0 nm (CRIRES setup 36). This particular setting was chosen because we could benefit from the CO 2 telluric atmospheric lines as simultaneous wavelength calibrators (Huélamo et al 2008;Figueira et al 2010c) to derive precise RVs. Previous studies have indeed shown that telluric lines are steady RV zero-point tracers (Figueira et al 2010b) that display a long-term stability and, for this reason, can deliver RVs with a precision down to 5-10 ms −1 .…”
Section: Observational Methods and Data Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spectra were collected using the 4096 × 512 pixel Aladdin III detectors and a 0.2" slit which delivered a R∼100000 around 1598.0 nm (CRIRES setup 36). This particular setting was chosen because we could benefit from the CO 2 telluric atmospheric lines as simultaneous wavelength calibrators (Huélamo et al 2008;Figueira et al 2010c) to derive precise RVs. Previous studies have indeed shown that telluric lines are steady RV zero-point tracers (Figueira et al 2010b) that display a long-term stability and, for this reason, can deliver RVs with a precision down to 5-10 ms −1 .…”
Section: Observational Methods and Data Reductionmentioning
confidence: 99%
“…Wavelength calibration was performed using telluric absorption lines (see e.g., Figueira et al 2010c;Bailey et al 2012). Laboratory wavelength zero-points of each telluric spectral line were collected from the HITRAN database (Rothman & Gordon 2009).…”
Section: Observational Methods and Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the observations, the telluric lines are superimposed on the stellar spectra, and Seifahrt et al (2008) showed that these atmospheric lines are stable in terms of velocity in the order of 10 m s −1 . Figueira et al (2010) adopted telluric lines as a stable wavelength reference, and showed that these lines allow us to reach RV precisions that are even better than 10 m s −1 when accounting for the changing weather conditions at the observatory during the observations. Special lamps that produce a dense forest of emission lines are used with most of the high-precision and stabilized spectrographs in the optical.…”
Section: Instrumental Limitationsmentioning
confidence: 99%
“…Bean et al (2010) conducted high-resolution data of 31 M-dwarfs (spectral types M4-M9), and report an RV precision of better than 5 m s −1 . Figueira et al (2010) took observations of the planetary candidate TW Hya and achieved a RV precision better than 10 m s −1 by adopting telluric lines as a stable reference. However, the exploration of the RVs in the IR is in its infancy, and a revolution is expected in the forthcoming years with the arrival of the new generation of high-resolution nearinfrared spectrographs.…”
Section: Introductionmentioning
confidence: 99%